POST-HERCYNIAN PLATE REORGANIZATION IN THE TETHYS AND ARCTIC – NORTH ATLANTIC DOMAINS - Ziegler P.A. (My University, 1988)
During the late phases of the Hercynian orogeny convergence between Gondwana and Laurasia changed from a southeast – northwest direction to an essentially east – west one. Whilst during the Stephanian – Autunian crustal shortening persisted in the Appalachians the Variscan fold belt and its foreland became dissected by a system of wrench faults. These played an important role in the localization of rifts during the breakup of Pangea. The initial phase of the post-Hercynian plate reorganization, spanning some 90 Ma was governed by the Permo-Triassic southward propagation of the pre-existing Norwegian – Greenland Sea rift system and the westward propagation of the Tethys rift system. Gradual westward propagation of the Neo-Tethys sea-floor spreading axis during the Late Triassic – Early Jurassic preceded the Middle Jurassic crustal separation between Laurasia and Africa. This marked the onset of the second phase of the post-Hercynian plate reorganization which was governed by the northward and southward propagation of the Central Atlantic sea-floor spreading system. The Late Jurassic and Cretaceous opening of the Central Atlantic was coupled with a counterclockwise rotation of Africa relative to Laurasia, inducing the closure of the Dinaric – Hellenic ocean and the early Alpine orogenic phases.
Keywords: Cretaceous; Triassic; Jurassic; Mesozoic::Triassic; Mesozoic::Jurassic; Mesozoic::Cretaceous; Мезозой::Юрская; Мезозой::Триасовая; Мезозой::Меловая